Dynamic fragmentation process and fragment microstructure evolution of alumina particles in a vacuum kinetic spraying system. (November 2015) - Park, Hyungkwon; Kim, Jinyoung; Lee, Changhee
Graphical abstract: Abstract: In a vacuum kinetic spraying (VKS) system, submicron ceramic particles impact the substrate and undergo dynamic fragmentation within nano-seconds, resulting in a nano grain film. In this report, a hypothesized mechanism for dynamic fragmentation generated during Al2 O3 particle deposition is suggested and tested via Auto-dyn simulation linked to an analysis of distinct fragment microstructures and debris size calculations. Based on this data, shock-induced dynamic fragmentation, one of the crucial elements of clarifying the deposition mechanism, was investigated.